PEMANFAATAN LIMBAH CAIR PABRIK KELAPA SAWIT UNTUK MEMENUHI KEBUTUHAN UNSUR HARA DALAM BUDIDAYA TANAMAN JAGUNG (Zea Mays L.) - Hendryx Wahyudi; Adnan Kasry; Is Sulistyati Purwaningsih (Program Pascasarjana Universitas Riau, 2011)
The purpose of this research was to see the opportunity of palm oil waste water utilization forreplacing anorganic fertilizer in growing crops. This research was using complete randomdesign in factorial design experiment using 12 kilograms of Podsolik that is mixed and filledin 40 x 40 centimeters plastic bags. Treatment that is used in this research was using wastewater Biological Oxygen Demand (BOD5) concentration (1000, 3000, 5000 and 7000)milligram per liter and urea fertilizer with dosage (0, 1, 2 and 3) gram and each treatmentwas three times replicated. The research was starting from February 28, 2010 to May 9,2010.Palm oil waste water that was used in this research gave significant difference result.Test result gave different result at all levels of waste water concentration except atconcentration of 3000 mg/l with 1000 mg/l. Interaction between treatment given was testedwith Duncan method and indicated that optimum dosage that can be used was 0 gram ofUrea fertilizer combained with waste water with BOD5 concentration 7000 mg/l.Utilizationof palm oil mill’s waste water with dosage 375 ml for 8 weeks after planting period orequivalent with 3 liters was not able to give crop result as good as comparison plant that isplanted, but waste water utilization to grow crop give good growth responses especially inmaize (Zea mays L.) that is tested. Utilization of palm oil’s waste water was suitable forbiomass production purposes but not for crop results. Utilization of palm oil mill’s wastewater especially in palm oil mill that has no plantation become one of solutions and efforts inreducing potential environmental damage caused by palm oil mill’s waste water, especiallywater and waterworks pollutions . It could be happen since waste water was not thrown awayto river but utilized to grow crops.